Photosensitive resin composition, dry film, cured product, and printed circuit board

JP2026166293APending Publication Date: 2026-10-14TAIYO HOLDINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059149
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、十分な剛性を有していながらも、解像性が良好な樹脂層を形成可能である感光性樹脂組成物、およびそれを用いたドライフィルム、硬化物、およびプリント配線板を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166293000001
    Figure 2026166293000001
  • Figure 2026166293000002
    Figure 2026166293000002
Patent Text Reader

Abstract

To provide a photosensitive resin composition that can form a resin layer with good resolution while having sufficient rigidity, and a dry film, cured product, and printed circuit board using the same. [Solution] A photosensitive resin composition comprising a carboxyl group-containing resin, a photopolymerization initiator, a thermosetting resin, and a filler, wherein the elastic modulus of the filler is 200 GPa or more, at least a portion of the surface of the filler is coated with an inorganic material, and the refractive index of the inorganic material at 365 nm is 1.2 to 1.7.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a photosensitive resin composition, a dry film, a cured product, and a printed circuit board. [Background technology]

[0002] Printed circuit boards (PCBs) used in electronic devices are substrates on which circuit patterns for electronic circuits are formed, and various components are mounted on them. When components are mounted on a PCB with exposed copper wires, there is a possibility of the copper wires breaking due to external force, or short circuits occurring due to solder adhering to areas other than the circuit pattern. Therefore, a protective layer called solder resist is formed to protect the circuit pattern and prevent short circuits.

[0003] Solder resist is formed, for example, using a photosensitive resin composition by an alkaline development method (see, for example, Patent Document 1). The alkaline development method involves laminating a resin layer formed from a photosensitive resin composition onto a substrate, partially curing this resin layer by exposure, and then developing the uncured resin layer with an alkaline aqueous solution to form a circuit pattern. Because the alkaline development method can also be used to form fine circuit patterns, it is used in the manufacture of printed circuit boards. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2007-49064 [Overview of the project] [Problems that the invention aims to solve]

[0005] In recent years, mobile devices and other electronic devices have been rapidly becoming smaller and thinner. Accordingly, there is a demand for miniaturization and thinning of the individual components used in these devices, and printed circuit boards (PCBs) are also required to be thinner. However, thinning PCBs can sometimes lead to problems such as deformation of the PCB itself when external force is applied. To address this problem, it was required to improve the rigidity of the solder resist.

[0006] Photosensitive resin compositions used to form solder resists typically contain fillers. Conventional photosensitive resin compositions use fillers such as silica (SiO2), but to further improve the rigidity of the solder resist, it is conceivable to use a filler with a higher modulus of elasticity than silica, such as a highly elastic filler like aluminum oxide (alumina). However, because highly elastic fillers have a significantly different refractive index from the resin components commonly found in photosensitive resin compositions, light can be scattered within the resin layer during exposure, potentially leading to a deterioration in resolution.

[0007] The present invention has been made based on these circumstances, and its objective is to provide a photosensitive resin composition that can form a resin layer with good resolution while having sufficient rigidity, and a dry film, cured product, and printed circuit board using the same. [Means for solving the problem]

[0008] In other words, the photosensitive resin composition according to the present invention is A photosensitive resin composition comprising a carboxyl group-containing resin, a photopolymerization initiator, a thermosetting resin, and a filler, The elastic modulus of the filler is 200 GPa or higher. At least a portion of the filler surface is coated with an inorganic material. The inorganic material is characterized by having a refractive index of 1.2 to 1.7 at 365 nm.

[0009] Further, in an aspect of the present invention, the thickness of the inorganic material is preferably 1,000 nm or less.

[0010] Further, in an aspect of the present invention, the inorganic material is preferably silica or barium sulfate.

[0011] Further, in an aspect of the present invention, the filler is preferably at least one selected from aluminum oxide, zirconium dioxide, and silicon nitride.

[0012] Further, a dry film according to another aspect of the present invention is characterized by having a resin layer formed from the above-described photosensitive resin composition.

[0013] Further, a cured product according to another aspect of the present invention is characterized by being obtained from the above-described photosensitive resin composition or the resin layer.

[0014] Further, a printed wiring board according to another aspect of the present invention is characterized by having the above-described cured product. [Effects of the Invention]

[0015] According to the present invention, it is possible to provide a photosensitive resin composition capable of forming a resin layer with good resolution while having sufficient rigidity, as well as a dry film, a cured product, and a printed wiring board using the same. [Modes for Carrying Out the Invention]

[0016] Hereinafter, the photosensitive resin composition, the dry film, the cured product, and the printed wiring board according to the present embodiment will be described.

[0017] (Photosensitive Resin Composition) The photosensitive resin composition contains a carboxyl group-containing resin, a photopolymerization initiator, a thermosetting resin, and a filler, and further contains other components as necessary.

[0018] <Carboxyl group-containing resin> The carboxyl group-containing resin is a resin having a carboxyl group in the molecule, and various conventionally known resins can be used. When the curable resin composition contains the carboxyl group-containing resin, developability (alkali developability) can be imparted to the curable resin composition. In particular, a carboxyl group-containing resin having an ethylenically unsaturated double bond in the molecule is preferred from the viewpoints of photocurability and development resistance. The ethylenically unsaturated double bond is preferably derived from acrylic acid, methacrylic acid, or a derivative thereof. Note that when only a carboxyl group-containing resin having no ethylenically unsaturated double bond is used, in order to make the curable resin composition photocurable, it is necessary to use in combination a compound having a plurality of ethylenically unsaturated groups in the molecule, which will be described later, that is, a photosensitive monomer.

[0019] Specific examples of the carboxyl group-containing resin include the following compounds (which may be either oligomers or polymers). These may be used alone or in combination of two or more.

[0020] (1) A carboxyl group-containing resin obtained by copolymerization of an unsaturated carboxylic acid such as (meth)acrylic acid and an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, and isobutylene.

[0021] (2) A carboxyl group-containing urethane resin obtained by a polyaddition reaction of a diisocyanate such as aliphatic diisocyanate, branched aliphatic diisocyanate, alicyclic diisocyanate, or aromatic diisocyanate, a carboxyl group-containing dialcohol compound such as dimethylolpropionic acid or dimethylolbutanoic acid, and a diol compound such as polycarbonate-based polyol, polyether-based polyol, polyester-based polyol, polyolefin-based polyol, acrylic polyol, bisphenol A-based alkylene oxide adduct diol, or a compound having a phenolic hydroxyl group and an alcoholic hydroxyl group.

[0022] (3) A partially acid anhydride modified product of a reaction between diisocyanate and a bifunctional epoxy resin such as bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bixylenol type epoxy resin, or biphenol type epoxy resin, and a monocarboxylic acid compound having an ethylenically unsaturated double bond such as (meth)acrylic acid, as well as a carboxyl group-containing photosensitive urethane resin obtained by polyaddition reactions of carboxyl group-containing dialcohol compounds and diol compounds.

[0023] (4) A carboxyl group-containing photosensitive urethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as hydroxyalkyl (meth)acrylate, during the synthesis of the resin of (2) or (3) above, and then (meth)acrylicating the terminal (meth)acrylic.

[0024] (5) A carboxyl group-containing photosensitive urethane resin in which a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule is added to the resin of (2) or (3) above during synthesis and then (meth)acrylicated at the terminal.

[0025] (6) A carboxyl group-containing resin obtained by reacting a bifunctional or polyfunctional (solid) epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride to the hydroxyl groups present in the side chain.

[0026] (7) A carboxyl group-containing resin obtained by reacting a polyfunctional epoxy resin, in which the hydroxyl groups of a bifunctional (solid) epoxy resin are further epoxidized with epichlorohydrin, with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups.

[0027] (8) A carboxyl group-containing polyester resin obtained by reacting a bifunctional oxetane resin with dicarboxylic acids such as adipic acid, phthalic acid, and hexahydrophthalic acid, and adding dibasic acid anhydrides such as phthalic anhydride, tetrahydrophthalic anhydride, and hexahydrophthalic anhydride to the resulting primary hydroxyl groups.

[0028] (9) A carboxyl group-containing resin obtained by reacting an epoxy compound having multiple epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenethyl alcohol, and an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and then reacting the alcoholic hydroxyl group of the reaction product with a polybasic acid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or adipic anhydride.

[0029] (10) A carboxyl group-containing resin obtained by reacting a reaction product obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.

[0030] (11) A carboxyl group-containing resin obtained by reacting a reaction product obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.

[0031] (12) A carboxyl group-containing resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to the resins of (1) to (11) above.

[0032] In this specification, (meth)acrylate is a general term referring to acrylates, methacrylates, and mixtures thereof, and the same applies to other similar expressions.

[0033] The acid value of the carboxyl group-containing resin is preferably 40 mg KOH / g to 150 mg KOH / g, and more preferably 50 mg KOH / g to 130 mg KOH / g. Setting the acid value of the carboxyl group-containing resin to 40 mg KOH / g or higher improves alkali developability. Furthermore, setting the acid value to 150 mg KOH / g or lower can improve resolution.

[0034] The weight-average molecular weight of carboxyl group-containing resins varies depending on the resin skeleton, but is generally preferably between 2,000 and 150,000, and more preferably between 5,000 and 100,000. A weight-average molecular weight of 2,000 or higher can improve tack-free performance and resolution. Furthermore, a weight-average molecular weight of 150,000 or lower can improve developability and storage stability. The weight-average molecular weight can be determined from the standard polystyrene equivalent value obtained by gel permeation chromatography (GPC).

[0035] The carboxyl group-containing resin content in the photosensitive resin composition is preferably 10% to 60% by mass, and more preferably 10% to 50% by mass, based on solid content. A content of 10% by mass or more can improve the strength of the cured product. Furthermore, a content of 60% by mass or less results in appropriate viscosity and improved printability.

[0036] <Photopolymerization initiator> The photopolymerization initiator is not particularly limited as long as it is one that is commonly used in photosensitive resin compositions, and can be appropriately selected depending on the purpose; any known one can be used.

[0037] Photopolymerization initiators, for example, bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide Bisacylphosphine oxides such as bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine methyl ester, 2-methylbenzoyldiphenylphosphine oxide, and pivaloylphenylphosphine isopropyl Monoacylphosphine oxides such as esters, 2,4,6-trimethylbenzoyldiphenylphosphine oxide; ethyl phenyl(2,4,6-trimethylbenzoyl)phosphinate, 1-hydroxycyclohexylphenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2-hydroxy- Hydroxyacetophenones such as 2-methyl-1-phenylpropan-1-one; benzoins such as benzoin, benzyl, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, and benzoin n-butyl ether; benzoin alkyl ethers; benzophenones such as benzophenone, p-methylbenzophenone, Michlar's ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, and 4,4'-bisdiethylaminobenzophenone;Acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 1,2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-( Acetophenones such as 4-morpholinyl)phenyl]-1-butanone and N,N-dimethylaminoacetophenone; thioxanthones such as thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, and 2,4-diisopropylthioxanthone; anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-ter Anthraquinones such as t-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, and 2-aminoanthraquinone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzoic acid esters such as ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoate ethyl ester; 1,2-octanedione, 1-[4-(phenylthio)phenyl]-,2-(O-benzoyl benzoate) Oxime esters such as sym, etanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-,1-(O-acetyloxime); titanosenes such as bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1H-pyrrole-1-yl)ethyl)phenyl]titanium;Examples include phenyl disulfide 2-nitrofluorene, butyroin, anisoin ethyl ether, azobisisobutyronitrile, and tetramethylthiuram disulfide. Among these, acetophenone-based, thioxanthone-based, anthraquinone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators are preferred. These may be used individually or in combination of two or more.

[0038] The content of photopolymerization initiators, excluding oxime ester-based photopolymerization initiators, is preferably 0.01 to 30 parts by mass, and more preferably 0.1 to 20 parts by mass, per 100 parts by mass of carboxyl group-containing resin, on a solid content basis. The content of the oxime ester-based photopolymerization initiator is preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 3.9 parts by mass, per 100 parts by mass of the carboxyl group-containing resin, on a solid content basis.

[0039] <Thermosetting resin> Thermosetting resins are not particularly limited as long as they are resins that harden (polymerize) upon heating, and can be appropriately selected according to the purpose. Examples of thermosetting resins include well-known and commonly used ones such as isocyanate compounds, blocked isocyanate compounds, amino resins, maleimide compounds, benzoxazine resins, carbodiimide resins, cyclocarbonate compounds, epoxy resins, oxetane compounds, and episulfide resins. These may be used individually or in combination of two or more. Among these, epoxy resins are preferred.

[0040] Examples of epoxy resins include bisphenol A type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin, brominated bisphenol A type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, and triphenylmethane type epoxy resin. These can be used individually or in combination of two or more different types.

[0041] There are no particular restrictions on the content of the thermosetting resin, and it can be appropriately selected depending on the purpose. Preferably, it is 10 to 80 parts by mass, and more preferably 20 to 70 parts by mass, in terms of solid content, per 100 parts by mass of the carboxyl group-containing resin.

[0042] <Filler> Fillers are included to improve the rigidity of the cured product obtained from the photosensitive resin composition. Preferably, at least a portion of the filler's surface is covered with an inorganic material, and the entire surface of the filler is covered with an inorganic material.

[0043] The elastic modulus of the filler is 200 GPa or higher, preferably 300 GPa or higher, and more preferably 350 GPa or higher. The upper limit of the elastic modulus of the filler is not particularly limited, but for example, it is preferably 1,000 GPa or less, more preferably 800 GPa or less, and even more preferably 600 GPa or less. If the elastic modulus of the filler is 200 GPa or higher, the rigidity of the cured product will be good.

[0044] The filler is not particularly limited as long as its elastic modulus is 200 GPa or higher, and can be appropriately selected according to the purpose. Examples include aluminum oxide (alumina), zirconium dioxide, and silicon nitride. These may be used individually or in combination of two or more. Among these, aluminum oxide is preferred due to its high elastic modulus.

[0045] There are no particular restrictions on the shape of the filler, and it can be appropriately selected depending on the purpose, but a spherical shape is preferred in terms of high filling capacity.

[0046] The volume-average particle size of the filler is preferably 0.01 μm to 5 μm, and more preferably 0.01 μm to 1 μm. The volume-average particle size can be determined as the median diameter (d50, volume-based) based on the cumulative distribution from the measured particle size distribution using the laser diffraction / scattering method with a commercially available laser diffraction / scattering particle size distribution analyzer.

[0047] <<Inorganic materials>> By coating the surface of the filler described above, the inorganic material can reduce the difference in refractive index between the filler and the resin component in the photosensitive resin composition. The refractive index of inorganic materials at 365 nm is 1.2 to 1.7, with 1.4 to 1.65 being preferred. When the refractive index is within this range, resolution is improved.

[0048] The refractive index of the inorganic material was measured using an Abbe refractometer (2010 / M prism coupler, manufactured by Metricon) on 2g of compressed inorganic material, under conditions of 589.3nm (D line) and 25°C.

[0049] Inorganic materials are not particularly limited as long as their refractive index at 365 nm is between 1.2 and 1.7, and can be appropriately selected according to the purpose. Examples include silica and barium sulfate. These can be used individually or in combination of two or more.

[0050] The thickness of the inorganic material is preferably 1,200 nm or less, and more preferably 1,000 nm or less. The lower limit of the inorganic material thickness is preferably 1 nm or more, more preferably 20 nm or more, and even more preferably 50 nm or more. When the thickness of the inorganic material is within the above range, the resolution is good.

[0051] The inorganic filler content is 50% to 80% by mass, based on solid content, relative to the entire photosensitive resin composition, preferably 60% to 80% by mass, and more preferably 65% ​​to 78% by mass. When the inorganic filler content is 50% by mass or more, the rigidity of the cured product tends to be good. When the inorganic filler content is 80% by mass or less, the embedding properties of the resin and the resolution upon development tend to be good.

[0052] <Other ingredients> Other components are not particularly limited as long as they are commonly used in photosensitive resin compositions and can be appropriately selected according to the purpose. Examples include colorants, thermosetting catalysts, and photosensitive monomers. Furthermore, if necessary, components such as ion scavengers, thixotropic agents, adhesion promoters, block copolymers, chain transfer agents, polymerization inhibitors, copper damage inhibitors, antioxidants, rust inhibitors, thickeners, defoamers, leveling agents, silane coupling agents, and flame retardants can be added. These can be those known in the field of electronic materials.

[0053] <<Coloring agent>> The coloring agent is not particularly limited as long as it is one that is commonly used in photosensitive resin compositions, and can be appropriately selected according to the purpose. Conventional and known coloring agents such as black, red, blue, green, yellow, and white can be used, and may be pigments, dyes, or colorants.

[0054] Examples of black colorants include carbon black, zirconium nitride, and Pigment Black 1, 6, 7, 8, 9, 10, 11, 12, 13, 18, 20, 25, 26, 28, 29, 30, 31, and 32. Examples of red colorants include monoazo, disazo, azolake, benzimidazolon, perylene, diketopyrrolopyrrole, condensed azo, anthraquinone, and quinacridone. Blue colorants include phthalocyanine-based and anthraquinone-based compounds, while pigment-based compounds classified as pigments can be used. In addition to these, metal-substituted or unsubstituted phthalocyanine compounds can also be used. Green coloring agents include phthalocyanine-based, anthraquinone-based, and perylene-based compounds. In addition to these, metal-substituted or unsubstituted phthalocyanine compounds can also be used. Examples of yellow colorants include monoazo, disazo, condensed azo, benzimidazolone, isoindolinone, and anthraquinone. Examples of white colorants include rutile or anatase titanium dioxide. In addition, colorants such as purple, orange, and brown may be added to adjust the color tone.

[0055] There are no particular restrictions on the amount of colorant, and it can be appropriately selected depending on the purpose. For example, 0.1 to 20 parts by mass, and more preferably 1 to 15 parts by mass, are preferred in terms of solid content, per 100 parts by mass of carboxyl group-containing resin.

[0056] <<Thermosetting catalyst>> Examples of thermosetting catalysts include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide and sebacate acid dihydrazide; and phosphorus compounds such as triphenylphosphine. Furthermore, S-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-2,4-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine isocyanuric acid adduct, and 2,4-diamino-6-methacryloyloxyethyl-S-triazine isocyanuric acid adduct can also be used, and preferably these compounds that also function as adhesion imparters are used in combination with the thermosetting catalyst. These may be used individually or in combination of two or more.

[0057] The amount of thermosetting catalyst is not particularly limited and can be appropriately selected depending on the purpose. For example, 1 to 30 parts by mass, and more preferably 1 to 20 parts by mass, is preferred in terms of solid content, per 100 parts by mass of carboxyl group-containing resin.

[0058] <<Photosensitive monomer>> Photosensitive monomers are monomers having an ethylenically unsaturated double bond. Examples of such photosensitive monomers include conventionally known polyester (meth)acrylates, polyether (meth)acrylates, urethane (meth)acrylates, carbonate (meth)acrylates, epoxy (meth)acrylates, and the like. Specifically, alkyl acrylates such as 2-ethylhexyl acrylate and cyclohexyl acrylate; hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate; mono- or diacrylates of alkylene oxide derivatives such as ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol; acrylamides such as N,N-dimethylacrylamide, N-methylolacrylamide, and N,N-dimethylaminopropylacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; hexanediol, trimethylolpropane, pentaerythritol, ditrimethylolpropane, dipentaerythritol, and trishydroxyethyl Examples include polyhydric acrylates derived from polyhydric alcohols such as isocyanurates or their alkylene oxide adducts or ε-caprolactone adducts; polyhydric acrylates derived from phenols such as phenoxyacrylate and bisphenol A diacrylate or their alkylene oxide adducts; acrylates derived from glycidyl ethers such as glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and, not limited to the above, acrylates obtained by directly acrylateting polyols such as polyether polyols, polycarbonate diols, hydroxyl-terminated polybutadienes, and polyester polyols, or by urethane acrylate obtained via diisocyanates, as well as melamine acrylate and methacrylates corresponding to the acrylates. These may be used individually or in combination of two or more.

[0059] The content of the photosensitive monomer is not particularly limited and can be appropriately selected depending on the purpose. For example, per 100 parts by mass of carboxyl group-containing resin, 1 to 40 parts by mass is preferred, 3 to 30 parts by mass is more preferred, and 5 to 20 parts by mass is even more preferred, in terms of solid content.

[0060] <Organic solvents> The photosensitive resin composition of the present invention may contain organic solvents for purposes such as preparing the composition or adjusting its viscosity when applying it to a substrate or film. Organic solvents that can be used include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These organic solvents may be used individually or in combination of two or more.

[0061] There are no particular restrictions on the content of the organic solvent; it can be appropriately selected depending on the desired viscosity.

[0062] <Method for producing a photosensitive resin composition> The method for producing the photosensitive resin composition is not particularly limited. For example, the above-mentioned components can be blended in predetermined proportions and then kneaded or mixed at room temperature using a kneading means such as a three-roll mill, ball mill, bead mill, or sand mill, or a stirring means such as a super mixer or planetary mixer. Furthermore, pre-kneading or pre-mixing may be performed before the aforementioned kneading or mixing, if necessary.

[0063] (Dry film) The dry film according to this embodiment comprises a first film and a resin layer, and further comprises other components as necessary.

[0064] <Resin layer> The resin layer is formed on the first film and consists of the aforementioned photosensitive resin composition. Here, the resin layer refers to a layer obtained by coating and drying the photosensitive resin composition, without any other layers such as the first film or other components laminated on it. There are no particular restrictions on the thickness of the resin layer; it can be selected as appropriate depending on the purpose.

[0065] <First Film> The first film (hereinafter also referred to as the "support film") has the role of supporting the resin layer of the dry film, and is coated with the photosensitive resin composition when forming the resin layer made of the photosensitive resin composition. In the present invention, when a dry film is laminated onto a substrate such as a circuit board by heating or other means so that the resin layer side of the dry film is in contact with the substrate, it refers to a film that is at least adhered to the resin layer. The first film may be peeled off from the resin layer in a process after lamination.

[0066] The first film can be any known film without particular limitations, and for example, films made of thermoplastic resins such as polyester films (polyethylene terephthalate, polyethylene naphthalate, etc.), polyimide films, polyamide-imide films, polypropylene films, and polystyrene films can be suitably used. Among these, polyester films are preferred from the viewpoint of heat resistance, mechanical strength, and ease of handling. Laminates of these films can also be used as the first film.

[0067] Furthermore, from the viewpoint of improving mechanical strength, it is preferable that the film made of thermoplastic resin is stretched in one or two directions.

[0068] When using a thermoplastic resin film as the first film, a film with a specific surface morphology may be used, achieved by adding a filler to the resin during film formation (mixing treatment), applying a matte coating (coating treatment), performing a blast treatment such as sandblasting on the film surface, or applying a hairline finish or chemical etching.

[0069] The thickness of the first film is not particularly limited, but can be, for example, 10 μm to 150 μm.

[0070] <Other components> Other components are not particularly limited as long as they are those used in ordinary dry films, and can be appropriately selected according to the purpose, for example, a second film.

[0071] <<Second Film>> The second film (hereinafter also referred to as the "protective film") is a film that is laminated for purposes such as preventing dust from adhering to the surface of the resin layer. Specifically, it is a film that is peeled off from the resin layer before lamination when laminating a dry film onto a substrate such as a circuit board by heating or other means so that the resin layer side of the dry film is in contact with the substrate.

[0072] The second film can be, for example, polyethylene film, polytetrafluoroethylene film, polypropylene film, or surface-treated paper. The adhesive strength of the second film to the resin layer should be less than the adhesive strength between the resin layer and the first film. Because the adhesive strength of the second film is less than that of the first film, the second film can be peeled off without moving the first film.

[0073] The thickness of the second film is not particularly limited, but can be, for example, 10 μm to 150 μm.

[0074] <Method for manufacturing dry film> The dry film is obtained by diluting the above-mentioned photosensitive resin composition with an organic solvent to adjust it to an appropriate viscosity, and then applying it to a first film to a uniform thickness using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, applicator, etc., and drying it at a temperature of 50°C to 130°C for 1 to 30 minutes. There are no particular restrictions on the coated film thickness, but generally, the film thickness after drying is appropriately selected within the range of 1 μm to 150 μm, preferably 5 μm to 60 μm.

[0075] (cured product) The cured product according to the embodiment is obtained by curing the above-mentioned photosensitive resin composition or the resin layer of the above-mentioned dry film. There are no particular restrictions on the size or shape of the cured product; it can be selected as appropriate depending on the purpose.

[0076] As a method for manufacturing the cured product, for example, the photosensitive resin composition of the present invention is adjusted to a viscosity suitable for the coating method using an organic solvent, and then applied to a substrate by methods such as dip coating, flow coating, roll coating, bar coating, screen printing, or curtain coating. After that, the organic solvent contained in the composition is evaporated and dried (pre-dried) at a temperature of 60 to 100°C for 15 to 90 minutes to form a tack-free resin layer. In the case of a dry film, the resin layer is bonded to the substrate using a laminator or the like so that the resin layer is in contact with the substrate, thereby forming a resin layer on the substrate.

[0077] Examples of substrates include printed circuit boards and flexible printed circuit boards with circuits pre-formed using copper, etc., copper-clad laminates using fluororesin, polyethylene, polyphenylene ether, polyphenylene oxide, cyanate, etc., metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate films, glass substrates, ceramic substrates, and wafers.

[0078] After forming a resin layer on a substrate, it is selectively exposed with active energy rays through a photomask on which a predetermined circuit pattern has been formed, and the unexposed areas are developed with a dilute alkaline aqueous solution (e.g., 0.3-3% by mass sodium carbonate aqueous solution) to form the circuit pattern. In the case of a dry film, after exposure, the first film is peeled off from the dry film and developed to form a patterned cured product on the substrate. Alternatively, if the properties are not impaired, the first film may be peeled off from the dry film before exposure, and the exposed resin layer may be exposed and developed. Furthermore, the cured product may be irradiated with active energy rays (e.g., 500 mJ / cm²). 2 ~3,000 mJ / cm 2 By heat curing (for example, 100-220°C) after the initial curing, or by irradiating with active energy rays after heat curing, or by performing final finishing curing (main curing) by heat curing alone, a cured product with excellent properties such as adhesion and hardness is formed.

[0079] The exposure machine used for active energy irradiation can be any device that emits ultraviolet light in the 350nm to 450nm range and is equipped with a high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, mercury short-arc lamp, etc. Furthermore, a direct writing device (for example, a laser direct imaging device that directly draws images with a laser using CAD data from a computer) can also be used. The lamp light source or laser light source of the direct writing device should have a maximum wavelength of 350nm to 450nm. The exposure amount for image formation varies depending on the thickness and size of the cured material, but is generally 10mJ / cm². 2 ~1000 mJ / cm 2 Preferably, 20 mJ / cm 2 ~800 mJ / cm 2 This is preferable.

[0080] Development methods include dipping, showering, spraying, and brushing. As for the developing solution, alkaline aqueous solutions such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, and amines can be used.

[0081] (Printed circuit board) A printed circuit board according to one embodiment of the present invention has a cured product of the above-mentioned photosensitive resin composition. There are no particular restrictions on the size or type of printed circuit board; they can be selected as appropriate for the purpose. [Examples]

[0082] Next, we will describe the tests conducted by the inventors, but the present invention is not limited to these.

[0083] (Examples 1-6, Comparative Examples 1-5) The materials were blended in the proportions shown in Table 1, pre-mixed in a stirrer, and then kneaded in a three-roll mill to prepare a photosensitive resin composition. The values ​​in the table are based on solid content. The units in the table are parts by mass.

[0084] [Table 1]

[0085] The details of each component in Table 1 are as follows: The carboxyl group-containing resin used was synthesized by the following method. In an autoclave equipped with a thermometer, nitrogen introduction device, alkylene oxide introduction device, and stirring device, 119.4 parts by mass of novolac-type cresol resin (Shonol CRG951, manufactured by Aica Kogyo Co., Ltd., OH equivalent: 119.4), 1.19 parts by mass of potassium hydroxide, and 119.4 parts by mass of toluene were introduced. The system was then purged with nitrogen while stirring, and the temperature was increased. Next, 63.8 parts by mass of propylene oxide were gradually added dropwise at 125°C to 132°C, at a rate of 0 kg / cm³. 2 ~4.8 kg / cm 2 The reaction was carried out for 16 hours. After cooling to room temperature, potassium hydroxide was neutralized by adding and mixing 1.56 parts by mass of 89% phosphoric acid to the reaction solution to obtain a propylene oxide reaction solution of novolac-type cresol resin [solid content: 62.1%; hydroxyl value: 182.2 mg KOH / g (307.9 g / eq.)]. This propylene oxide reaction solution contained an average of 1.08 moles of propylene oxide added per equivalent of phenolic hydroxyl groups. 293.0 parts by mass of the propylene oxide reaction solution of the obtained novolac-type cresol resin, 43.2 parts by mass of acrylic acid, 11.53 parts by mass of methanesulfonic acid, 0.18 parts by mass of methylhydroquinone, and 252.9 parts by mass of toluene were introduced into a reactor equipped with a stirrer, thermometer, and air blowing tube. Air was blown in at a rate of 10 ml / min, and the mixture was reacted at 110°C for 12 hours while stirring. 12.6 parts by mass of water produced by the reaction was distilled off as an azeotropic mixture with toluene. The mixture was then cooled to room temperature, neutralized with 35.35 parts by mass of 15% aqueous sodium hydroxide solution, and then washed with water. Subsequently, toluene was removed by distillation with 118.1 parts by mass of diethylene glycol monoethyl ether acetate in an evaporator, while substituting for the toluene, to obtain a novolac-type acrylate resin solution. Next, 332.5 parts by mass of the obtained novolac-type acrylate resin solution and 1.22 parts by mass of triphenylphosphine were introduced into a reactor equipped with a stirrer, thermometer, and air blowing tube. Air was blown in at a rate of 10 ml / min, and while stirring, 60.8 parts by mass of tetrahydrophthalic anhydride were gradually added. The mixture was reacted at 95°C to 101°C for 6 hours, and after cooling, it was removed to obtain a carboxyl group-containing resin solution (solids content: 65% by mass, acid value of solids: 87.7 mg KOH / g). • Photopolymerization initiators (acylphosphine oxide-based photopolymerization initiators, 2,4,6-trimethylbenzoyldiphenylphosphine oxide) • Thermosetting resin (N-730-A, manufactured by DIC Corporation, phenol novolac type epoxy resin) • Thermosetting resin (N-870, manufactured by DIC Corporation, phenol novolac type epoxy resin, dilution solution of diethylene glycol monoethyl ether acetate, solids content 75% by mass) · Filler 1 (Aluminum oxide coated with SiO2 to a thickness of 200 nm; modulus of elasticity of aluminum oxide: 380 GPa; refractive index of SiO2 at 365 nm: 1.47) 100 parts by mass of aluminum oxide particles (ASFP-20, manufactured by Denka Co., Ltd., average particle size 0.3 μm, specific gravity 4.0) were mixed with 40 parts by mass of isopropanol (IPA), and then 20 parts by mass of tetraethoxysilane (TEOS: a precursor of silica, which is the surface composition) was added. After reacting at room temperature for 24 hours, the mixture was neutralized with aqueous ammonia to obtain a gel-like precipitate consisting of constituent primary particles. The precipitate was washed with pure water, dried at 160°C for 2 hours, and then ground to an average particle size of 2 μm or less using a jet mill to obtain filler 1. • Filler 2 (Zirconium oxide coated with SiO2 to a thickness of 200 nm; modulus of elasticity of zirconium oxide: 200 GPa; refractive index of SiO2 at 365 nm: 1.47) Filler 2 was obtained in the same manner as in the method for producing Filler 1, except that aluminum oxide particles were replaced with zirconium oxide (manufactured by Kojun Chemical Laboratory Co., Ltd.). · Filler 3 (Silicon nitride coated with SiO2 to a thickness of 200 nm; elastic modulus of silicon nitride: 300 GPa; refractive index of SiO2 at 365 nm: 1.47) Filler 3 was obtained in the same manner as in the method for producing filler 1, except that aluminum oxide particles were replaced with boron nitride particles (manufactured by ESK Ceramics GmbH). · Filler 4 (Aluminum oxide coated with BaSO4 to a thickness of 200 nm; modulus of elasticity of aluminum oxide: 380 GPa; refractive index of BaSO4 at 365 nm: 1.64) • Filler 5 (aluminum oxide coated with SiO2 to a thickness of 1,000 nm; elastic modulus of aluminum oxide: 380 GPa; refractive index of SiO2 at 365 nm: 1.47) 100 parts by mass of aluminum oxide particles (ASFP-20, manufactured by Denka Co., Ltd., average particle size 0.3 μm, specific gravity 4.0) were mixed with 40 parts by mass of isopropanol (IPA), and then 100 parts by mass of tetraethoxysilane (TEOS: a precursor of silica, which is the surface composition) was added. After reacting at room temperature for 24 hours, the mixture was neutralized with aqueous ammonia to obtain a gel-like precipitate consisting of constituent primary particles. The precipitate was washed with pure water, dried at 160°C for 2 hours, and then ground to an average particle size of 2 μm or less using a jet mill to obtain filler 5. · Filler 6 (Aluminum oxide coated with SiO2 to a thickness of 1,200 nm; modulus of elasticity of aluminum oxide: 380 GPa; refractive index of SiO2 at 365 nm: 1.47) 100 parts by mass of aluminum oxide particles (ASFP-20, manufactured by Denka Co., Ltd., average particle size 0.3 μm, specific gravity 4.0) were mixed with 40 parts by mass of isopropanol (IPA), and then 120 parts by mass of tetraethoxysilane (TEOS: a precursor of silica, which is the surface composition) was added. After reacting at room temperature for 24 hours, the mixture was neutralized with aqueous ammonia to obtain a gel-like precipitate consisting of constituent primary particles. The precipitate was washed with pure water, dried at 160°C for 2 hours, and then ground to an average particle size of 2 μm or less using a jet mill to obtain filler 6. • Filler 7 (SO-C2, manufactured by Admatex Co., Ltd.) (SiO2 filler with no inorganic coating on the surface; modulus of elasticity of SiO2: 72 GPa) • Filler 8 (aluminum oxide, manufactured by Denka Co., Ltd., ASFP-20, average particle size 0.3 μm, specific gravity 4.0) (Aluminum oxide filler with no inorganic coating on the surface; modulus of elasticity of aluminum oxide: 380 GPa) • Filler 9 (Zirconium oxide, manufactured by Kojun Chemical Laboratory Co., Ltd., average particle size 1 μm, specific gravity 5.68) (Zirconium oxide filler with no inorganic coating on the surface; modulus of elasticity of zirconium oxide: 200 GPa) • Filler 10 (Silicon nitride, manufactured by Denka Co., Ltd., SN-9FWS, average particle size 0.7 μm, specific gravity 3.18) (Silicon nitride filler with no inorganic coating on the surface; elastic modulus of silicon nitride: 300 GPa) · Filler 11 (Aluminum oxide coated with zirconium oxide to a thickness of 200 nm; modulus of elasticity of aluminum oxide: 380 GPa; refractive index of zirconium oxide at 365 nm: 2.3) A 50g aqueous slurry of zirconium oxide (manufactured by Kojun Chemical Laboratory Co., Ltd., average particle size 1 μm, specific gravity 5.68) was heated to 70°C, and then 10% sodium silicate aqueous solution was added to the aluminum oxide particles at a concentration of 1% per aluminum oxide particle. Hydrochloric acid was added to this slurry to adjust the pH to 4, and it was aged for 30 minutes. Then, while maintaining the pH at 5±1 with hydrochloric acid, the temperature was raised to 40°C, and 100g / l zirconium oxychloride aqueous solution was added to the aluminum nitride particles at a concentration of 1% per aluminum oxide particle (based on ZrO2). After this, a 20% sodium hydroxide aqueous bath was added to adjust the pH to 7, and it was aged for 30 minutes. After this, the slurry was filtered and washed with water using a filter press, vacuum dried, and aluminum oxide filler 11 coated with silicon hydrate oxide and zirconium hydrate oxide was obtained. <<Other ingredients>> • Photosensitive monomer (DPHA (dipentaerythritol hexaacrylate), manufactured by Nippon Kayaku Co., Ltd.) • Thermosetting catalyst (dicyandiamide) • Yellow pigment (CIPigment Yellow 147) • Blue pigment (CIPigment Blue 15:3)

[0086] <Preparation of dry film> Each of the obtained photosensitive resin compositions was applied using an applicator onto a 38 μm polyethylene terephthalate film (T-60, manufactured by Toray Industries, Inc.) to a dry film thickness of 20 μm, and dried at 80°C for 20 minutes to obtain a dry film.

[0087] The resolution and elastic modulus of the obtained dry films were evaluated as described below. The evaluation results are shown in Table 2.

[0088] The optimal exposure amount for the obtained dry film was determined as follows. A copper plated sheet (Cu plated sheet, manufactured by Nippon CMK Co., Ltd.) was pre-treated using a pre-treatment agent (CZ8100, manufactured by MEC Co., Ltd.). Each dry film was then bonded to this substrate using a vacuum laminator so that the resin layer, made of a photosensitive resin composition, was in contact with the substrate, thereby forming a resin layer on the substrate. This substrate was exposed using an exposure apparatus equipped with a high-pressure mercury short-arc lamp via a step tablet (Stuffer 41 steps), and the optimal exposure amount was determined when the pattern of the remaining step tablet after development (30°C, 0.2 MPa, 1 mass% Na2CO3 aqueous solution) for 60 seconds resulted in 8 steps.

[0089] <Resolution> A Cu-plated plate (manufactured by Nippon CMK Co., Ltd.) was pretreated using a pretreatment agent (CZ8100, manufactured by MEC Co., Ltd.). Each dry film was laminated using a vacuum laminator such that the resin layer composed of the photosensitive resin composition was in contact with the substrate, to form a resin layer on the substrate. Using an exposure apparatus equipped with a high-pressure mercury short arc lamp, the solder resist on this substrate was pattern-exposed at L / S=100 / 100 μm at the optimal exposure amount determined above, then the polyester film was peeled off, and development was performed for 60 seconds under the conditions of a spray pressure of 0.2 MPa using a 1 mass% Na2CO3 aqueous solution at 30°C, to obtain a patterned cured product. This substrate was subjected to a cumulative exposure of 1,000 mJ / cm in a UV conveyor furnace 2 after being irradiated with ultraviolet rays under the conditions, and then heated at 170°C for 60 minutes to be cured. The L / S pattern shape of the obtained evaluation substrate was subjected to cross-sectional observation using an SEM (JSM-6610LV BEC, manufactured by JEOL Ltd.) under the conditions of an applied voltage of 20 kV and a magnification of 1,000 times, and the resolution was evaluated based on the following evaluation criteria. -Evaluation Criteria- ◯: Error is less than 10 μm Δ: Error is 10 μm or more and less than 15 μm ×: Error is 15 μm or more

[0090] <Elastic Modulus> On the glossy surface side (copper foil) of a copper foil (GTS-MP foil, manufactured by Furukawa Circuit Foil Co., Ltd.), each dry film was laminated using a vacuum laminator such that the resin layer composed of the photosensitive resin composition was in contact with the substrate, to form a resin layer on the copper foil. This was exposed at the above optimal exposure amount using an exposure apparatus equipped with a high-pressure mercury short arc lamp, and then the polyester film was peeled off. This was subjected to a cumulative exposure of 1,000 mJ / cm in a UV conveyor furnace 2 after being irradiated with ultraviolet rays under the conditions, and then heated at 170°C for 60 minutes to be cured, to obtain a cured product. Thereafter, the cured product was peeled from the copper foil, and then cut into a size of 50 mm × 10 mm × 20 μm to obtain a sample. The sample was subjected to a tensile tester (AG-X, manufactured by Shimadzu Corporation), the elastic modulus at 25°C was measured at a tensile speed of 1 mm / sec, and the elastic modulus was evaluated based on the following evaluation criteria. -Evaluation Criteria- ○: Storage modulus of 10 GPa or higher at 25°C ×: Storage modulus less than 10 GPa at 25°C

[0091] [Table 2]

[0092] When the photosensitive resin compositions of Examples 1 to 6 were applied to a substrate and cured, the cured products received evaluation results of "○" or "△" for resolution and elastic modulus. In contrast, Comparative Examples 1 to 4, which used fillers whose surfaces were not coated with inorganic materials, received an evaluation of "×" for resolution. Furthermore, Comparative Example 5, which used a filler coated with an inorganic material having a refractive index of 2.3, also received an evaluation of "×" for elastic modulus. From these results, it became clear that by using a filler with an elastic modulus of 200 GPa or higher, and whose surface is coated with an inorganic material having a refractive index of 1.2 to 1.7 at 365 nm, a photosensitive resin composition that achieves both resolution and elastic modulus can be provided.

[0093] Furthermore, in Examples 1 to 5, where the inorganic material thickness was 1,000 nm or less, the resolution and elastic modulus evaluation results were all "○", whereas in Example 6, where the inorganic material thickness was 1,200 nm, the resolution evaluation result was "△". From this, it can be said that a photosensitive resin composition with an inorganic material thickness of 1,000 nm or less is better able to achieve both resolution and elastic modulus.

[0094] Although embodiments for carrying out the present invention have been specifically described above, the present invention is not limited thereto and can be modified in various ways without departing from its essence.

Claims

1. A photosensitive resin composition comprising a carboxyl group-containing resin, a photopolymerization initiator, a thermosetting resin, and a filler, The elastic modulus of the filler is 200 GPa or more. At least a portion of the surface of the filler is covered with an inorganic material. A photosensitive resin composition characterized in that the refractive index of the inorganic material at 365 nm is 1.2 to 1.

7.

2. The photosensitive resin composition according to claim 1, wherein the thickness of the inorganic material is 1,000 nm or less.

3. The photosensitive resin composition according to claim 1, wherein the inorganic material is silica or barium sulfate.

4. The photosensitive resin composition according to claim 1, wherein the filler is at least one selected from aluminum oxide, zirconium dioxide, and silicon nitride.

5. A dry film having a resin layer formed from the photosensitive resin composition described in claim 1.

6. A cured product obtained from the photosensitive resin composition described in claim 1 or the resin layer described in claim 5.

7. A printed circuit board having the cured product described in claim 6.

Citation Information

Patent Citations

  • Insulating hardenable composite and its curing object, and printed wiring board using it

    JP2007049064A